Graphical Separation Performance-Exergy Analysis for Revamping of Distillation Column - Budiman, Arief (ASEAN Journal of Chemical Engineering, 2008)
We have invented graphical representation of separation performance and the exergy loss of all subprocesses in a distillation column on material-utilization diagram (MUD). The diagram display flowrate of liquid and gas as abscissa and ln x and ln y as ordinate. This diagram is useful for qualifying and quantifying the exergy loss in a distillation column, since exergy gain and exergy loss in the liquid and gas phases as well as in the phase change, can be displayed in a single figure. This paper is proposed to apply this MUD for revamping of distillation column.